2015
DOI: 10.1007/s00705-015-2626-5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and evolutionary history of lettuce necrotic yellows virus in Australia and New Zealand

Abstract: Lettuce necrotic yellows virus (LNYV) is the type member of the genus Cytorhabdovirus, family Rhabdoviridae, and causes a severe disease of lettuce (Lactuca sativa L.). This virus has been described as endemic to Australia and New Zealand, with sporadic reports of a similar virus in Europe. Genetic variability studies of plant-infecting rhabdoviruses are scarce. We have extended a previous study on the variability of the LNYV nucleocapsid gene, comparing sequences from isolates sampled from both Australia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…Many studies conducted on other genus revealed similar results with insufficient molecular studies of Anthemideae (Matousek et al, 2007;Garcia et al, 2010;Riggins and Seigler, 2012). Similar results were obtained by other authors (Riggins and Seigler, 2012;Patil et al, 2016;Higgins et al, 2016;Kumar et al, 2016).…”
Section: Resultssupporting
confidence: 87%
“…Many studies conducted on other genus revealed similar results with insufficient molecular studies of Anthemideae (Matousek et al, 2007;Garcia et al, 2010;Riggins and Seigler, 2012). Similar results were obtained by other authors (Riggins and Seigler, 2012;Patil et al, 2016;Higgins et al, 2016;Kumar et al, 2016).…”
Section: Resultssupporting
confidence: 87%
“…Similarly, sequencing and phylogenetic analysis of the complete N gene of eight LNYV isolates from Australia also showed no temporal separation in subgroups [10]. However, this is in contrast to later studies of LNYV which reported the clustering of more recently collected isolates in a subgroup, with older isolates forming a distinct clade [23]. Table 1.…”
Section: Soybean Blotchy Mosaic Virus (Sbbmv) Is Provisionally Classimentioning
confidence: 80%
“…As an example, the high variability and absence of isolates from Lusikisiki in Groups A and C and the limited presence of isolates from Schoemanskloof in the other groups might be the result of competitive exclusion. Enhanced interactions of isolates in Groups A and C with plant or insect hosts may lead to their apparent dominance, as also described in Lettuce necrotic yellows virus (LNYV) [23]. Soybean cultivar selection varies greatly in different regions, as does the natural vegetation, which may serve as alternative hosts, and these may act in strain selection, furthermore insect vectors often select for specific genotypes adapted to plant-vector systems [24].…”
Section: Soybean Blotchy Mosaic Virus (Sbbmv) Is Provisionally Classimentioning
confidence: 99%
“…In our study, all RSMV isolates showed low genetic variability (less than 1% at the nt level, Table 3; and the variation rates were mostly below 1.0%, Figure 3). However, lettuce necrotic yellow virus (LNYV) was found to form two subgroups and differed significantly between them (about 20% at the nt and 4% at the aa level) based on the analysis of the N gene (Higgins et al, 2016), whereas the N gene sequence of Taro vein chlorosis virus isolates differed significantly between them (19.3% at the nt and 6.3% at the aa level) (Revill et al, 2005). This may indicate some evidence that RSMV is a “new” pathogen that emerged and dispersed recently.…”
Section: Discussionmentioning
confidence: 99%